The Impact of Enterobiasis on Some Blood Elements among Children in Tikrit City - Al-Shaima M. Jasim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Enterobiasis caused by Enterobius vermicularis is a widespread intestinal parasitic infection that commonly affects children and has been associated with nutritional disorders and hematological abnormalities. Specific Background: The infection may interfere with digestion, absorption, and micronutrient balance, potentially contributing to anemia and deficiencies of essential elements such as ferritin, magnesium, zinc, and vitamin B12. Knowledge Gap: Despite the high prevalence of enterobiasis in developing regions, limited empirical data exist on the variations in hematological and biochemical parameters among infected children in Tikrit City. Aims: This study aimed to examine the relationship between Enterobius vermicularis infection and selected blood elements among children aged 2–10 years in Tikrit City between April 2023 and April 2024. Results: Among 100 examined children, 75% were infected with E. vermicularis. The infection rate was slightly higher in males (78.72%) than females (71.69%), and higher in children aged 6–10 years (80.39%) than those aged 2–5 years (69.38%). Infected children showed significantly lower hemoglobin levels (10.610 ± 1.21 g/dl) compared with non-infected children (11.724 ± 0.767 g/dl). Significant reductions were also observed in serum ferritin (28.5 ± 4.51 ng/ml vs 37.5 ± 5.73 ng/ml), magnesium (1.433 ± 0.180 mg/dl vs 1.992 ± 0.138 mg/dl), zinc (48.77 ± 9.85 mg/dl vs 62.59 ± 8.43 mg/dl), and vitamin B12 (485.0 ± 56.0 pg/ml vs 623.6 ± 33.3 pg/ml). Novelty: The study provides detailed evidence of multiple hematological and micronutrient variations associated with E. vermicularis infection among children in Tikrit City. Implications: These findings highlight the need for early diagnosis, routine monitoring of blood parameters, and strengthened health awareness programs to reduce infection spread and related nutritional complications. Highlights:• High Prevalence of Pinworm Infection Observed Among Examined Children in Tikrit City• Infected Participants Showed Lower Hemoglobin and Multiple Micronutrient Concentrations• Monitoring Hematological and Biochemical Indicators Supports Early Clinical Management Keywords: Enterobius Vermicularis, Enterobiasis, Hemoglobin, Micronutrient Deficiency, Children Health